Importance Teachings About New Heaven and Earth - Benny Zakaria; Aprianus L. Moimau (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
The second coming of Christ is an event inalienable to mankind. In addition to declaring punishment for unbelievers, His second coming also fulfills the presence of a new heaven and earth in which the righteous will reign with Christ forever. Of this, the Bible records that